Investigation of morphological and structural properties of V incorporated SnSe2 single crystals. (15th June 2018) - Zankat, Chetan K.; Pataniya, Pratik; Solanki, G.K.; Patel, K.D.; Pathak, V.M.; Som, Narayan; Jha, Prafulla K.
Abstract: The unique ternary compositions Vx Sn1-x Se2 (x = 0, 0.15, 0.25 and 0.5) have been grown in single crystal form by direct vapour transport technique. The as-grown crystals have been examined under Carl Zeiss optical microscope for morphological studies. The tiny flakes have also been observed by scanning electron microscope and it reveals the layered structure of as-grown ternary alloys. The powder XRD pattern infers hexagonal lattice structure with 2H poly type and P 3 ¯ m 1 space group. The XRD pattern shows shifting of diffraction peaks on higher angle side as content of vanadium (V) increases, confirms substitution of V-atoms on tin (Sn)-atom sites. Using transmission electron microscope, the nano-structures have been found in sono-chemically exfoliated samples. The selected area electron diffraction pattern has been obtained using 200 kV electron beam and reveals the single crystalline nature of Vx Sn1-x Se2 (x = 0, 0.15, 0.25 and 0.5) ternary alloys. The Raman spectra show SnSe2 type A1g and Eg vibrational modes and on increasing V content blue shift in A1g peak indicates that the V-atoms well substitutes on Sn-site.